2022
DOI: 10.1007/s12602-022-09928-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Activity of Antimicrobial Peptides Against Common Marine Bacteria Located in Rotifer (Brachionus plicatilis) Cultures

Abstract: Rotifers are used as the first feed for marine fish larvae and are grown in large cultures that have high loads of organic matter and heterotrophic bacteria; these bacteria are passed on to the developing fish larvae and can potentially lead to bacterial infections. A modified minimum inhibitory concentration (MIC) protocol for antimicrobial peptides was used to determine the potency of ten antimicrobial peptides (AMPs) in artificial seawater relevant to a rotifer culture (salinity of 25‰) against common marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Rotifers are small-sized live preys, and non-selective filters, that are crucial for delivering essential nutrients and probiotics to underdeveloped fish larvae. Currently, all rotifers are enriched before being supplied to fish larvae, not only to meet nutritional demands, but also to enhance growth, survival rates, and stress tolerance, and promote microbial diversity [19][20][21][22][23][24]. Nevertheless, the rearing tank of rotifer cultures has been recognized as an optimal environment for the growth of pathogenic and opportunistic bacteria, such as Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotifers are small-sized live preys, and non-selective filters, that are crucial for delivering essential nutrients and probiotics to underdeveloped fish larvae. Currently, all rotifers are enriched before being supplied to fish larvae, not only to meet nutritional demands, but also to enhance growth, survival rates, and stress tolerance, and promote microbial diversity [19][20][21][22][23][24]. Nevertheless, the rearing tank of rotifer cultures has been recognized as an optimal environment for the growth of pathogenic and opportunistic bacteria, such as Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, strategies to disinfect and clean rotifers of unwanted opportunistic and pathogenic bacteria are a topic of growing interest. However, such strategies have often had a lethal result on the rotifers or yielded inconclusive results [22][23][24]. On the other hand, several authors have previously demonstrated the benefits of enriching rotifers with probiotic bacteria in finfish larviculture systems.…”
Section: Introductionmentioning
confidence: 99%